Rozprzestrzenianie się płaskich Fal Sprężysto-Plastycznych Wywołanych Udarem Masowym - Włodarczyk, E. (Engineering Transactions, 1970)
In this paper the one-dimensional motion of a column of soil, is investigated, emplaced in a non-deformable cylinder covered from the top by a disk having mass m2 and loaded by falling mass m1 with velocity ν0, and on which there acts a constant pressure p0 (Fig. 1). The solution of the problem is given for the curvilinear relationship σ = σ(ε) with rigid unloading and for a medium with linear hardening. On the basis of the solution obtained the conditions of mass shock have been established at which it is possible to generate a stationary pressure wave loading the sample of soil under investigation. The results of this paper will form the basis for the design for a suitable test stand designated to determine the velocities of propagation of elasto-plastic stress waves in granular soils.